On the resonance values of the dynamical stress in the system comprises two-axially pre-stretched layer and half-space - Tasci, Fatih; Emiroglu, Ibrahim; Akbarov, Surkay D. (SPRINGER, 2007)
This paper is devoted to the study of the influence of the pre-stretching of a covering layer on the resonance values of a stress. The investigations are performed within the framework of the piecewise homogeneous body model with the use of the Three Dimensional Linearized Theory of Elastic Waves in Initially Stressed Bodies (TLTEWISB). Numerical results are presented for some selected materials.
Keywords: elastic waves; bi-axially pre-stretch layer; resonance; PRESTRETCHED LAYER; PLANE; SURFACE; FIELD; Engineering; Mechanics